2021
DOI: 10.3390/mi12060648
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Hybrid Nanostructures for Dimethyl Methyl Phosphonate Detection

Abstract: Nanostructured materials synthesized by the hydrothermal and thermal reduction process were tested to detect the dimethyl methylphosphonate (DMMP) as a simulant for chemical warfare agents. Manganese oxide nitrogen-doped graphene oxide with polypyrrole (MnO2@NGO/PPy) exhibited the sensitivity of 51 Hz for 25 ppm of DMMP and showed the selectivity of 1.26 Hz/ppm. Nitrogen-doped multi-walled carbon nanotube (N-MWCNT) demonstrated good linearity with a correlation coefficient of 0.997. A comparison between a surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The response times ( T 90 ) can be explained as the time taken to attain 90% of the equilibrium, whereas the recovery time is the time taken to reach 10% of the equilibrium via purging with the dry nitrogen [ 67 ]. Figure S15 illustrates the response and recovery time of the hybrid composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response times ( T 90 ) can be explained as the time taken to attain 90% of the equilibrium, whereas the recovery time is the time taken to reach 10% of the equilibrium via purging with the dry nitrogen [ 67 ]. Figure S15 illustrates the response and recovery time of the hybrid composites.…”
Section: Resultsmentioning
confidence: 99%
“…For both the composites, the recovery times were longer than the response times. The reversible response also indicates that the adsorption of DMMP onto the sensing materials consists of weak hydrogen bonding or Van der Waals forces [ 67 , 68 ]. The performance comparison was conducted with a composite-material-coated QCM sensor for the detection of DMMP as shown in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it may have caused the volumetric changes, allowing a small portion of the sensing material to fall off the CE surface [ 57 ]. The fast recovery of the QCM sensor when the QCM sensor was purged with nitrogen showed that the interaction between the sensing materials and DMMP was the weak force of attraction or hydrogen bonding [ 19 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of the 250 MHz SAW sensor is reported elsewhere [ 10 , 19 , 40 , 41 ]. CE, MnO 2 @CE, and MnO 2 @CE/PPy were mixed with IPA at a 1 mg:7 mL ratio because SAW sensors are highly susceptible to the weight of the deposited sensing materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation